The Connexion between Old and New Approaches to Financial Satisfaction - Bernard M.S. Van Praag (Tinbergen Institute, 2004)
In this paper we compare the new satisfaction evaluation approach, developed inthe nineties by Oswald ,Clark , Blanchflower and others with the older incomeevaluation (IEQ) approach, developed by Van Praag and Kapteyn in theseventies of the previous century. We find that both approaches yield strikinglysimilar results with respect to financial satisfaction. The IEQ-approach yieldsadditional insights, but it is not well applicable to other life domains thanfinance. It is argued that the usual Probit specification implies a specificcardinalization and, consequently, is less ordinal than usually thought. It isshown that the Probit-approach may be replaced by three other equivalentspecifications that have some computational and intuitive advantages.
Keywords: C24; C25; D31; H31; I31; I39; 330; Financial satisfaction; income evaluation; Probit-models; cardinal utility; Eigeninteresse; Nutzentheorie; Haushaltseinkommen